The Urgency of Establishing Regulations on the Implementation of Automatic Features as a Mitigation Measure Against the Distribution of Feature Films on the TikTok Platform - Esi Anindya Azzahra; Taupiqqurrahman Taupiqqurrahman (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the urgency of establishing regulations that require digital platforms, particularly TikTok, to implement automatic features as a mitigation effort against the illegal distribution of feature films. The background of this research is based on the phenomenon of increasing copyright infringements in the digital space due to the ease of access, distribution, and replication of content through user-generated content-based social media. This condition indicates a normative gap in Indonesia’s legal system, which has not explicitly regulated the preventive responsibilities of electronic system providers concerning intellectual property rights violations. The main issues examined include the existing legal regulations in Indonesia regarding the obligation to provide copyright infringement detection features, as well as the juridical basis for the necessity of establishing specific regulations under the Ministry of Communication and Digital Affairs. This study employs a normative juridical method with a statute approach and a literature review of legislation and Constitutional Court decisions. The findings show that existing regulations, such as the Copyright Law and Ministerial Regulations, remain reactive and have not yet regulated preventive obligations or mitigation measures for digital platforms. In conclusion, the establishment of technical regulations through a Ministerial Regulation is a juridical necessity to strengthen legal certainty and the effectiveness of copyright protection in the digital sphere. This research recommends that national policy stipulate minimum technical standards for implementing automatic detection systems on digital platforms, particularly TikTok.